PENGEMBANGAN MEDIA ZIGZAG BOOK BERBASIS MODEL CIRC UNTUK MENINGKATKAN KEMAMPUAN MENENTUKAN IDE POKOK PARAGRAF PADA SISWA KELAS V SDN 1 TAMANREJO - Ulfa Marya, Allifna; Nugraheti Sismulyasih Sb (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop a Zigzag Book learning media based on the CIRC (Cooperative Integrated Reading and Composition) model to improve the ability to determine the main idea of paragraphs in fifth-grade elementary school students. This research uses the Research and Development (R&D) method adapted from Borg and Gall's development model, which was modified into eight stages. The research subjects were fifth-grade students of SDN 1 Tamanrejo, with 5 students for small-scale trials and 12 students for large-scale trials. Data collection techniques used tests (pretest and posttest) and non-tests (interviews, observations, questionnaires, and documentation). The results showed that the developed Zigzag Book media received a "very feasible" category from material expert validation (95%) and media expert validation (93.33%). The results of the large-scale trial showed an increase in the average student score from 58.75 to 83.33. The paired sample t-test results obtained a significance value of 0.000 <0.05, and the N-Gain value was 0.5728 in the moderate category. Teacher and student response questionnaires also gave very positive results. Thus, the Zigzag Book media based on the CIRC model is declared feasible and effective for use in learning Indonesian.